Association between the dopamine transporter gene (DAT1) and attention deficit hyperactivity disorder-related traits in healthy adults. (June 2015) - Jeong, Seong Hoon; Choi, Keong-Sook; Lee, Kyu Young; Kim, Eui-Joong; Kim, Yong-Sik; Joo, Eun-Jeong
Abstract : Background: The dopamine transporter gene ( DAT1 ) is an established genetic risk factor for attention deficit hyperactivity disorder (ADHD). Therefore, we hypothesized that DAT1 may also influence the manifestation of ADHD-related traits in the normal population. Methods: A quantitative association study was carried out on 1289 healthy adults. ADHD-related traits were measured using the 25-item Wender Utah Rating Scale (WURS-25). This scale is a self-administered instrument intended to retrospectively measure features of childhood ADHD. Previous studies typically identified three component factors: (i) impulsivity, (ii) inattention, and (iii) mood instability. Our group found that these factors were associated with various diagnoses, such as bipolar disorder and major depression. Six polymorphic markers within the DAT1 gene (rs27072, rs11133767, rs429699, rs27048, rs2937639), including the 3′-untranslated region variable number of tandem repeats, were used as genetic markers. Results: The WURS-25 total score was not associated with any of the markers that we examined. However, the mood instability trait was associated significantly with rs2937639 in male participants ( P =0.008); this result was supported by several haplotype-wise findings among the surrounding markers ( P =0.00001–0.004). Conclusion: Our study results suggest that DAT1 polymorphisms may modulate mood instability traits in the normal population. Considering that mood instability tends to persist through the entire course of ADHD and is highly prevalent in many diseases that are comorbid with ADHD, this trait may be a core endophenotype that defines the role of the DAT1 gene in various psychiatric conditions.